Transforming the Irvine Ranch : Joan Irvine, William Pereira, Ray Watson, and the big plan - Stockstill, C. Michael; Oliver, H. Pike (New York, NY ; Abingdon, Oxon : Routledge, 2022)
"Transforming the Irvine Ranch tells the story of Orange County's metamorphosis from 93,000 acres of failing farmland into an iconic Southern California landscape of beaches and modernist architecture. This vivid chronicle draws on decades of archival research and the authors' time at the famed Irvine Company to bring the colorful characters responsible for the transformation to life. Spanning the history of modern California from its goldrush past to high tech present, this family and social history recounts the Irvine Company's largely successful attempts to remake the state in its own image"--
A decade of determination -- A planner's path: early life, education and real work -- Ray arrives at a company on the brink of change -- "We are not gods" -- Athalie -- Joan -- The birth of UC Irvine -- Inclusions, exclusions and the campus that never was -- Pipes and plans -- Defending the borders -- The campaign for cityhood -- The new city: partners or antagonists, or a little of both? -- The magic of planning -- From plans to reality: Eastbluff and Newport Center -- The Tax Reform Act of 1969 -- Acceleration -- Conflicting visions of the Upper Newport Bay -- Politics and media -- Low-cost housing: "a problem from day one" -- The jewel in the crown -- The best of all possible coasts -- Town and gown -- Joan redux -- Buying time -- Schout's honor -- Wise (and rich) men from the east -- Going all in -- Ray departs -- Villains no more -- The big plans of William Pereira -- Reasons for success -- Follow the money
OCLC-licensed vendor bibliographic record.
Keywords: Planned communities -- California -- Irvine Ranch -- History; Real estate development -- California -- Irvine Ranch -- History; Irvine Ranch (Calif.) -- History -- Chronology; Orange County (Calif.) -- History -- Chronology; BUSINESS & ECONOMICS / Real Estate; BUSINESS & ECONOMICS / Corporate & Business History